Population genetic structure of wild Malayan tapirs Tapirus indicus in Peninsular Malaysia revealed by nine cross-species microsatellite markers - Lim, Qi Luan; Yong, Christina Seok Yien; Ng, Wei Lun; Ismail, Ahmad; Rovie-Ryan, Jeffrine J.; Rosli, Norsyamimi; Inoue-Murayama, Miho; Annavi, Geetha (Elsevier B.V., 2022)
The Malayan tapir (Tapirus indicus) is an endangered species endemic to Southeast Asia. Previous research have used maternally inherited, mitochondrial DNA genetic markers to investigate the population genetics of the species but not the biparentally inherited, nuclear genetic markers. However, the increasing pressure of habitat fragmentation and roadkill on the Malayan tapirs has called for an urgent need to assess the species’ genetic status. In this study, the genetic diversity, population genetic structure, and sex-biased dispersal patterns of the tapir population in Peninsular Malaysia were investigated using nine cross-species microsatellite markers, using sixty-seven tapir samples (39 wild, 11 captive-born, and 17 of unknown origin) provided by the wildlife department, zoo and conservation centre. Low genetic diversity of the wild population was found based on heterozygosity and allelic richness, and a cryptic pattern of population genetic structure was inferred. One (K = 3) to two (K = 4) genetic clusters in proximity to the south-western part of the major forest complexes seemed to be experiencing restricted gene flows compared to the other more widespread clusters or clines. Effective to census population size was estimated at 0.39–0.46. Sex-biased dispersal was not found in the current dataset. Even though these results may need cautious interpretation due to possible sampling bias, this study is the first study that investigated the genetic diversity distribution for the species using nuclear markers, and therefore will have conservation implications for the implementation of the Central Forest Spine Master Plan in Peninsular Malaysia to connect major forest complexes.